The Quarterly Journal of Economics Volume 130 August 2015 Issue 3 - Front Cover (Quarterly Journal of Economics, 2015)
Journal Article The Quarterly Journal of Economics Volume 130 August 2015 Issue 3 - Front Cover Get access The Quarterly Journal of Economics, Volume 130, Issue 3, August 2015, Page i1, https://doi.org/10.1093/qje/qju050 Published: 10 July 2015